Expression of FRIGIDA in root inhibits flowering in Arabidopsis thaliana - Kong, Xiangxiang (Journal of experimental botany, 2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.